Personalised learning: lessons to be learnt. (25th January 2013) - Prain, Vaughan; Cox, Peter; Deed, Craig; Dorman, Jeffrey; Edwards, Debra; Farrelly, Cathleen; Keeffe, Mary; Lovejoy, Valerie; Mow, Lucy; Sellings, Peter; Waldrip, Bruce; Yager, Zali
<x xml:space="preserve">Abstract</x> Personalised learning is now broadly endorsed as a key strategy to improve student curricular engagement and academic attainment, but there is also strong critique of this construct. We review claims made for this approach, as well as concerns about its conceptual coherence and effects on different learner cohorts. Drawing on literature around differentiation of the curriculum, self‐regulated learning, and 'relational agency' we propose a framework for conceptualising and enacting this construct. We then report on an attempt to introduce personalised learning as one strategy, among several, to improve student academic performance and wellbeing in four low SES regional secondary schools in Australia. We report on a survey of 2407 students' perceptions of the extent to which their school provided a personalised learning environment, and a case study of a programme within one school that aimed to apply a personalised approach to the mathematics curriculum. We found that while there were ongoing challenges in this approach, there was also evidence of success in the mathematics case.